Registration and promotion of monumental olive trees in Greece. - Koniditsiotis, Stavros (Advances in Social Sciences Research Journal, 2020)
The history of the olive tree, its cultivation and its products is known for centuries. Some olive tree have survived over millennia and their history dates back to antiquity. In many cases, it is related to mythology and religion. The olive tree is associated with folk tradition, people’s everyday life, and customs. In Greece, monumental olive trees are found in the Peloponnese, Crete, Euboea, Chios, Pelion and Attica. This paper explores and describes the particular morphological features such as shape, size, wood, cavities and age, as well as the cultural characteristics such as historical or religious events, myths and traditions that define an olive tree and characterize it as monumental. The main aim of our research is to examine the key position that monumental olive trees and their materialistic and symbolic manifestations consist a natural and cultural heritage as well. In this framework the study focuses on various key issues related to monumental olives trees and their natural, historical, social and cultural value.